Reflections on training next-gen industry workforce on secure software development - Gasiba, T. E. (2023)
The increasing number of security incidents highlights the growing importance of cybersecurity, particularly in industrial environments. Education and awareness of secure coding practices are fundamental to secure products and services. In this paper, we explore the potential of CyberSecurity Challenges (CSCs), a serious game that is designed to raise awareness of industrial software developers about secure coding, to train the next generation of professionals in undergraduate programs. Our work details how to tailor the game to the training environment and assesses its effectiveness through an experiment undertaken with 16 trainees. The findings of our work reveal that the CSC game can contribute to raising awareness of secure coding practices among next-generation trainees, and highlights the potential that the game has when used in an academic setting.